The moderating effect of financial knowledge on financial risk tolerance - John E. Grable; Abed Rabbani (Journal of Risk and Financial Management, 2023)
The purpose of this paper is to describe a study that was designed to determine to what extent subjective and objective measures of financial knowledge moderate the relationship between an investor's financial risk tolerance and demographic factors thought to be important descriptors of an investor's willingness to take a financial risk. It was determined that those who identified as male, and those with more attained education and income, exhibited higher investment risk tolerance (IRT). Subjective financial knowledge (SFK) was positively associated with IRT. The relationship between gender and IRT was moderated by SFK, whereas the relationship between IRT and age was moderated by objective financial knowledge (OFK). A positive relationship between education and IRT was noted, but the relationship was moderated by OFK, whereas the association between IRT and household income was moderated by SFK. Findings from this study indicate that while SFK and OFK are positively correlated, they are not measuring the same underlying construct, and as such, each moderates IRT relationships differently.
Keywords: D90; D91; D14; D10; 650; financial knowledge; objective financial knowledge; risk tolerance; subjective financial knowledge